Pengaruh Kunjungan Wisatawan, Jumlah Tingkat Hunian Kamar Hotel, dan Jumlah Kamar Hotel Terhadap Pendapatan Asli Daerah (PAD) di Kabupaten Badung, Gianyar, Tabanan, dan Kota Denpasar Tahun 2001-2010 - Wijaya, Agung Satrya; Djayastra, I Ketut (E-Jurnal Ekonomi Pembangunan Universitas Udayana, 2014)
Regional income is a regional financial resources extracted from the relevant local area . Badung, Gianyar ,Tabanan and Denpasar is the county / city revenue contributor in the province of Bali and has a variety of attractions . This study aims to investigate the influence of tourist arrivals , number of hotel room occupancy rate , and number of hotel rooms to regional income in Badung , Gianyar , Tabanan and Denpasar years 2001-2010 . Types of data is a secondary data with the technique of multiple linear regression analysis (multiple regression). Results of the analysis indicated the influence of tourist arrivals and number of hotel rooms is positive and significant effect, while the number of hotel room occupancy rate is no significant effect to regional income in Badung ,Gianyar , Tabanan and Denpasar years 2001-2010.
Keywords: Pariwisata; hotel; wisatawan; pendapatan asli daerah